Mobile Versus Fixed Deployment of Automated External Defibrillators in Rural EMS. Issue 2 (27th February 2015) - Nelson, R. Darrell; Bozeman, William; Collins, Greg; Booe, Brian; Baker, Todd; Alson, Roy
Abstract: Introduction: There is no consensus on where automated external defibrillators (AEDs) should be placed in rural communities to maximize impact on survival from cardiac arrest. In the community of Stokes County, North Carolina (USA) the Emergency Medical Services (EMS) system promotes cardiopulmonary resuscitation (CPR) public education and AED use with public access defibrillators (PADs) placed mainly in public schools, churches, and government buildings. Hypothesis/Problem: This study tested the utilization of AEDs assigned to first responders (FRs) in their private-owned-vehicle (POV) compared to AEDs in fixed locations. Methods: The authors performed a prospective, observational study measuring utilization of AEDs carried by FRs in their POV compared to utilization of AEDs in fixed locations. Automated external defibrillator utilization is activation with pads placed on the patient and analysis of heart rhythm to determine if shock/no-shock is indicated. The Institutional Review Board of Wake Forest University Baptist Health System approved the study and written informed consent was waived. The study began on December 01, 2012 at midnight and ended on December 01, 2013 at midnight. Results: During the 12-month study period, 81 community AEDs were in place, 66 in fixed locations and 15 assigned to FRs in their POVs. No utilizations of the 66 fixed location AEDs were reported (0.0 utilizations/AED/year) while 19 utilizations occurred in the FR POV AED study group (1.27 utilizations/AED/year; P <.0001). Odds ratio of using a FR POV located AED was 172 times more likely than using a community fixed-location AED in this rural community. Discussion: Placing AEDs in a rural community poses many challenges for optimal utilization in terms of cardiac arrest occurrences. Few studies exist to direct rural community efforts in placing AEDs where they can be most effective, and it has been postulated that placing them directly with FRs may be advantageous. Conclusions: In this rural community, the authors found that placing AED devices with FRs in their POVs resulted in a statistically significant increase in utilizations over AED fixed locations. RD Nelson, W Bozeman, G Collins, B Booe, T Baker, R Alson .Mobile versus fixed deployment of automated external defibrillators in rural EMS .Prehosp Disaster Med .2015 ;30 (2 ):1 -3 .